Cumulative Damage: Cell Death in Posthemorrhagic Hydrocephalus of Prematurity - Riley Sevensky; Jessie C. Newville; Ho Lam Tang; Shenandoah Robinson; Lauren L. Jantzie (Cells, 2021)
Globally, approximately 11% of all infants are born preterm, prior to 37 weeks’ gestation. In these high-risk neonates, encephalopathy of prematurity (EoP) is a major cause of both morbidity and mortality, especially for neonates who are born very preterm (<32 weeks gestation). EoP encompasses numerous types of preterm birth-related brain abnormalities and injuries, and can culminate in a diverse array of neurodevelopmental impairments. Of note, posthemorrhagic hydrocephalus of prematurity (PHHP) can be conceptualized as a severe manifestation of EoP. PHHP impacts the immature neonatal brain at a crucial timepoint during neurodevelopment, and can result in permanent, detrimental consequences to not only cerebrospinal fluid (CSF) dynamics, but also to white and gray matter development. In this review, the relevant literature related to the diverse mechanisms of cell death in the setting of PHHP will be thoroughly discussed. Loss of the epithelial cells of the choroid plexus, ependymal cells and their motile cilia, and cellular structures within the glymphatic system are of particular interest. Greater insights into the injuries, initiating targets, and downstream signaling pathways involved in excess cell death shed light on promising areas for therapeutic intervention. This will bolster current efforts to prevent, mitigate, and reverse the consequential brain remodeling that occurs as a result of hydrocephalus and other components of EoP.